2021
DOI: 10.3390/nu13114119
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-Processed Food Dietary Pattern Is Associated with Lower Diet Quality in Portuguese Adults and the Elderly: The UPPER Project

Abstract: This study aimed to identify dietary patterns (DPs) and their associations with sociodemographic factors and diet quality in Portuguese adults and the elderly. Cross-sectional data were obtained from the National Food, Nutrition and Physical Activity Survey (2015–2016), with two non-consecutive dietary 24 h recalls. Food items were classified according to the NOVA system and its proportion (in grams) in the total daily diet was considered to identify DPs by latent class analysis, using age and sex as concomita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…In support of this, according to our earlier study conducted in 2013-2014, UPF were accounted for around 20 % of daily energy intake (Accepted article). In terms of other determinants of UPF intake, we found a positive association between educational level and UPF consumption and an inverse link between age and UPF consumption which were compatible with the results of other developed, high-income countries (14,15,28) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In support of this, according to our earlier study conducted in 2013-2014, UPF were accounted for around 20 % of daily energy intake (Accepted article). In terms of other determinants of UPF intake, we found a positive association between educational level and UPF consumption and an inverse link between age and UPF consumption which were compatible with the results of other developed, high-income countries (14,15,28) .…”
Section: Discussionsupporting
confidence: 90%
“…In the I.Family study, both children and adults with higher UPF intake consumed higher amounts of sugar and fat but lower amounts of fiber and protein (14). In Portuguese adults and the elderly, higher amounts of UPF consumption were associated with higher carbohydrates, saturated fats and sugar, while the intake of protein, fiber, vitamin A, vitamin C, folate, potassium, magnesium and iron was lower in comparison with a healthy traditional dietary pattern (15). Furthermore, in our subgroup analysis, NARs of calcium and magnesium were closely related to various lifestyle and socioeconomic variables.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These diets are rich in saturated fat and simple sugar, especially sucrose, and thus are comparable to the so-called "junk food" [40]. However, evaluation of the effects of Western diet on animal health is achieved by the constant consumption of these diets [11][12][13][14], which is not what normally happens [15]. In the current work, we have mimicked "cheat meal" consumption by giving to mice a HFHS diet once a week, somehow comparing it to people that sporadically eat "junk food".…”
Section: Discussionmentioning
confidence: 99%
“…For these studies, animals were subjected to a continuous longterm diet enriched in saturated fat and simple sugars. One feebleness of these studies, as compared to human Western diet ingesting regimen, is that, normally, the regular consumption is not continuous, but intercalated with different kinds of nourishments [15]. Nevertheless, different studies have reported that acute consumption of different high-fat and/or high-sucrose diets triggers similar responses to those observed in long-term ingestion [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%